À procura da liberdade. Fugas internacionais de escravos negros na fronteira oeste do Império do Brasil (1822-1867) - Newman di Carlo Caldeira (Centre de Recherches sur les Mondes Américains, 2009)
This article aims to present the development of the processes of legitimizing and protecting the slave property in Brazil, especially concerning Brazilian relationships with the Bolivian Republic. Diplomatic documentation shows the contradictions in the debate about the validation of property rights, claimed by Brazilian citizens, and the defence of the right to freedom, claimed by countries that gave asylum to those runaways.